2021
DOI: 10.3390/en14154614
|View full text |Cite
|
Sign up to set email alerts
|

Application of Graphene in Fiber-Reinforced Cementitious Composites: A Review

Abstract: Graphene with fascinating properties has been deemed as an excellent reinforcement for cementitious composites, enabling construction materials to be smarter, stronger, and more durable. However, some challenges such as dispersion issues and high costs, hinder the direct incorporation of graphene-based reinforcement fillers into cementitious composites for industrial production. The combination of graphene with conventional fibers to reinforce cement hence appears as a more promising pathway especially towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…Besides, the graphene market is also gradually expanding and relatively mature for industrialization due to the wide range of graphene applications. 158,159 Spent GA has been proved to have the advantages of low cost consumption and high yield in the process of graphene preparation. Therefore, it has a broad market prospect as a graphene raw material and can be applied on a large scale.…”
Section: Functional Composite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the graphene market is also gradually expanding and relatively mature for industrialization due to the wide range of graphene applications. 158,159 Spent GA has been proved to have the advantages of low cost consumption and high yield in the process of graphene preparation. Therefore, it has a broad market prospect as a graphene raw material and can be applied on a large scale.…”
Section: Functional Composite Materialsmentioning
confidence: 99%
“…Because of its stable change and easy handling, it can continue to be applied to energy storage systems without excessive processing. Besides, the graphene market is also gradually expanding and relatively mature for industrialization due to the wide range of graphene applications 158,159 . Spent GA has been proved to have the advantages of low cost consumption and high yield in the process of graphene preparation.…”
Section: Recycling Of Spent Gamentioning
confidence: 99%
“…A review of existing studies shows that the first attempts to regulate the electrical properties of cement matrices were first described in [ 10 , 11 ]. There are three types of electrically conductive structures formed in the mineral matrix: cluster [ 12 , 13 ], linear [ 14 ], and complex [ 15 ]. To obtain each of the types, different types of additives are used: finely dispersed powders, predominantly round in shape, and particles with relative elongation [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are three types of electrically conductive structures formed in the mineral matrix: cluster [ 12 , 13 ], linear [ 14 ], and complex [ 15 ]. To obtain each of the types, different types of additives are used: finely dispersed powders, predominantly round in shape, and particles with relative elongation [ 13 , 14 , 15 ]. Due to the peculiarities of the electrical conductivity [ 7 ] of the mineral matrix based on Portland cement, additives such as carbon-containing materials, fiber based on various types of metals, dispersed powders in the form of metal oxides or a mixture of doped oxides can be used to reduce the electrical resistivity [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have found that graphene outperforms other carbon materials in terms of electrical and thermal conductivity as well as weavability when used for fiber electrodes [22][23][24][25][26][27]. As an emerging material in the field of energy storage, graphene has shown the world its fascinating properties, such as high impermeability [28][29][30], high electron mobility [31], high thermal conductivity [32,33], superlubricity [34][35][36], extraordinary elasticity and stiffness [37,38]. Particularly, the high electrical conductivity of graphene sheets could avoid the inclusion of conductive additives and enhance the energy density of graphene-based electrodes.…”
Section: Introductionmentioning
confidence: 99%